2012
DOI: 10.1038/nmat3363
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the autophagy-inducing activity of lanthanide-based nanocrystals through specific surface-coating peptides

Abstract: The induction of autophagy on exposure of cells to a variety of nanoparticles represents both a safety concern and an application niche for engineered nanomaterials. Here, we show that a short synthetic peptide, RE-1, identified by means of phage display, binds to lanthanide (LN) oxide and upconversion nanocrystals (UCN), forms a stable coating layer on the nanoparticles' surface, and effectively abrogates their autophagy-inducing activity. Furthermore, RE-1 peptide variants exhibit a differentially reduced bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 44 publications
0
112
0
Order By: Relevance
“…First, the effects of the above synthesized NBPs with various surface coatings on autophagy were compared, as the surface chemistry of nanomaterials plays a vital role in their autophagy regulation function 12, 13. Among the four coated NBP samples, only the NBP/TiO 2 nanostructure induced dramatic increases in GFP‐LC3 puncta (Figure 1d) and LC3‐II expression (Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the effects of the above synthesized NBPs with various surface coatings on autophagy were compared, as the surface chemistry of nanomaterials plays a vital role in their autophagy regulation function 12, 13. Among the four coated NBP samples, only the NBP/TiO 2 nanostructure induced dramatic increases in GFP‐LC3 puncta (Figure 1d) and LC3‐II expression (Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
“…There has been growing interest in nanomaterials for autophagy regulation. Quantum dots,11 carbon nanotubes,12 lanthanide oxide,13 cerium oxide,14 titanium dioxide (TiO 2 ),15 and silver nanoparticles16 have been identified as autophagy inducers. However, nanomaterials for autophagy inhibition applications are still rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wen group [71][72][73][74] in University of Science and Technology of China made a series of excellent study on the toxicity of rare earth oxides nanomaterials, mainly focused on their impact on cellular autophagy (Table 3). They found that micromolar equivalent concentration of nano-sized neodymium oxide (Nano Nd 2 O 3 ) could induce autophagy and cell death in non-small cell lung cancer NCI-H460 cells.…”
Section: Rare Earth Oxides Nanomaterialsmentioning
confidence: 99%
“…And the autophagic response was dose-and time-dependent [72]. In another study, they investigated three rare earth oxides na- [74] achieved to control the ability of Ln 2 O 3 nanocrystals to induce autophagy via surface-coating peptides. In a screening assay they identified a short peptide RE-1 that could reduce Ln 2 O 3 induced autophagy.…”
Section: Rare Earth Oxides Nanomaterialsmentioning
confidence: 99%